POSSIBILITIES OF FORECASTING COMPLICATIONS IN PATIENTS WITH METABOLIC SYNDROME - Mustafayeva, A.H. (World of Medicine and Biology, 2021)
In the period from 2013 to 2016, 364 patients aged 20 to 80 years (200 men and 164 women) with newly diagnosed metabolic syndrome were prospectively examined. In patients aged 20–60 years and in the age group 61–80 years, the analysis of the results of the examination of patients with metabolic syndrome allowed us to build a number of regression models that allow predicting variants of metabolic syndrome: diabetic, hypertensive or combined. A study of the incidence of complications of metabolic syndrome showed that in the age group of 20–40 years the incidence of myocardial infarction was 1.9 % and that of ischemic stroke in 0.96 %, in the age group 41–60 years, respectively, 14.5 and 7.6 %; In the group of patients older than 60 years – myocardial infarction was observed in 12.9 % of patients, ischemic stroke in 6.7 % of cases. The analysis of the results of the examination of patients with metabolic syndrome allowed us to build a number of regression models that allow predicting variants of the metabolic syndrome. It has been shown that metabolic syndrome is a factor predisposing to atrial fibrillation and a favourable background for the implementation of risk factors for atrial fibrillation.
Keywords: metabolic syndrome; complications; regression analysis; prognostic parameters